Interaction between glycolysis‒cholesterol synthesis axis and tumor microenvironment reveal that gamma-glutamyl hydrolase suppresses glycolysis in colon cancer - Chen, Yan-Jie; Guo, Xi; Liu, Meng-Ling; Yu, Yi-Yi; Cui, Yue-Hong; Shen, Xi-Zhong; Liu, Tian-Shu; Liang, Li (Frontiers in Immunology, 2022)
Background: Since cancer features reprogramming cellular metabolism, whether colon cancer can be subtyped based on glycolysis-cholesterol synthesis axis and its connection with tumor microenvironment remain unknown. Methods: Four hundred and thirty colon cancer cases were extracted from The Cancer Genome Atlas with transcriptome data, clinical information, and survival outcome. Glycolysis and cholesterol synthesis related gene sets were obtained from the Molecular Signatures Database to perform the gene set variations analysis. The relationship between genomic landscape and immune landscape in colon cancer were investigated among four metabolic subtypes. Hub genes were determined. The clinical significance of candidate hub gene was evaluated in 264 clinical samples and its potential function were validated in vitro and in vivo. Results: Colon cancer cases were clustered into metabolic subtypes, including Quiescent, Glycolytic, Cholesterogenic, and Mixed. The metabolic subtypes differ from each other in aspect of ImmneScore, StromalScrore, EstimateScore, cancer-immunity cycle, immunomodulator signatures, and signatures of immunotherapy. Patients stratified into Cholesterogenic had a relative favorable survival outcome than others, especially for Glycolytic. Glycolytic related to unfavorable clinical characteristics, including high mutation rate of TTN, APC, and TP53, high mutation burden, vascular invasion, right colon cancer and low-frequency microsatellite instablility. GGH, CACNG4, MME, SLC30A2, CKMT2, SYN3, SLC22A31 were identified differently expressed and involved in glycolysis-cholesterol synthesis. GGH was upregulated in colon cancer, while its high expression not only appeared to correlated with CD4+ T cell infiltration, but also indicated longer overall survival and a favorable independent factor for patients with colon cancer. Overexpression of GGH in colon cancer derived cell lines (SW48, SW480) could inhibited the expression of PKM, GLUT1, and LDHA, and decreased extracellular lactate content and intracellular ATP level, while the opposite effect was confirmed when GGH was silenced. The phenotype of GGH was also validated in xenograft nude mice models. Conclusions: Our study gave insight into the potential connection of metabolism and tumor microenvironment in colon cancer and reveals the preliminary role of GGH along with mechanistic clues for subsequent studies.